HUBUNGAN ANTARA PENDIDIKAN, PENGETAHUAN, DAN SIKAP IBU BERSALIN DENGAN PRAKTEK PENCARIAN PERTOLONGAN PERSALINAN - Zulkarnain, Elfian; Luthviatin, Novia; Gayatri, Galuh (FKM - UNEJ, 2007)
Bear a child by baby indigenous medical practitioner still dominant in Indonesia. That matter caused by understanding and access of woman to service of health still lower. Low of understanding and acces of woman to service of health relating to perception and knowledge about health especially health of reproduction, status of woman, and level of education. The Purpose of this research is to analyze Â correlation between level of education, knowledge of KIA, and attitude of mother that will bear with practice seeking of help of rescuer of bear in region of Public Health Center in Rowotengah Sub District of Sumberbaru Distric of Jember. This research represent as surveying research with cross sectional approach and samples counted 90 peoples that taken with proportional random sampling method. Primary data on this research taken through test of interview. Result of this research indicate that there is relation between level of education of mother that will bear with practice with practice seeking of help of rescuer of bear, between mother attitude with Â practice seeking of help of rescuer of bear in region of Health Center in Rowotengah District of Sumberbaru Sub Province of Jember. Key words: education, knowledge, attitude, rescuer of bear